Detecting and Mitigating Repaying Attack in Expressive Internet Architecture (XIA) - Nugraha, Beny; Khondoker, Rahamatullah; Marx, Ronald; Bayarou, Kpatcha (Journal of ICT Standardization, 2014)
Several Future Internet (FI) architectures have been proposed to address the problems of the Internet including flexibility (so called IP bottleneck), host-based addressing (addressing a host rather than the content itself), and security. In the beginning of this article, we survey the security solutions of seven FI architectures, namely XIA, RINA, NENA, SONATE, Mobility-First, NDN, and SONATE, based on literatures, prototypes, and demonstrations. It has been found that none of the architectures can fulfill all of the security goals: confidentiality, authentication, integrity and availability. Further in this article, we focus on eXpressive Internet Architecture (XIA) as it is the most secure and open-source Content-Centric Network (CCN). CCN is claimed by the Future Content Networks (FCN) Group to be the Future Internet. However, XIA does not have any mechanisms to mitigate the replaying attack, thus, this article proposes and implements a solution to mitigate it. Several existing solutions have been analyzed to derive the requirements for the proposed solution. By implementing the proposed protocol, XIA is now able to mitigate all of the reviewed network attacks. The evaluation shows that the proposed solution is more secure and less complex over the existing solutions.